Combinational compatibility of large white breed pigs in individual genealogical lines and families - Голуб, Н. Д. (Scientific Progress & Innovations, 2013)
The article represents the aspects of reproductive and feed qualities of certain lines of boars and sows as well as their combinative ability to produce multiple births. The best combinations are installed between the boars genealogical lines of Gromkiy and Soya, Swat and Taiga, Shalun (VBUP) and Chernaya Ptichka –11 piglets and more. Due to the feed characteristics of boars and sows geniture there were showed good results. Average daily gains were obtained at 614–795 gram, the weight of 100–202 kg was achieved in 178 days, the working costs of foodstuff per 1kilo growth are 3.42 to 4.21 units. The best due to the feed qualities are the genealogical lines of SWAT, Gromkiy, Shalun, Orion male pigs and the large white breed boars of Danish origin.